PEMANFAATAN APLIKASI ANDROID BABY CARE SEBAGAI SOLUSI DALAM PENCATATAN TUMBUH KEMBANG ANAK - Mariza Devega; Fana Wiza (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2018)
The use of Smart Phone Android today is not only as a supporter of communication between humans, but also can be used like a laptop that is usually used in terms of searching for information, read news, and so forth. Baby care is an android application that serves to see the baby's record, ranging from growing flowers, vaccination, nutritional intake, milk, sleep duration and so on, besides this application replaces the manual recording function that is prone to damage and lost (Human eror) . Training This application aims to facilitate the mothers in seeing their children grow more detailed in effective and efficient, and at the same time replace the previous function which record manually. Keywords: Android Application, Baby Care, KMS